Effect of Date of Sowing and Crop Geometry on Growth and Production Potential of Cluster Bean under Rainfed Condition of Gujarat - Dhedhi, K. K.; Chaudhari, N. N.; Juneja, R. P.; Sorathiya, J. S. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted under rainfed condition during kharif seasons of 2013 and 2014 at Pearl millet Research Station, Junagadh Agricultural University, Jamnagar, Gujarat (India) to find out the optimum time of sowing and row spacing for production potential of cluster bean (var. Gujarat Guar 2). The experimental field was laid out in split plot design with four replications. There were six treatment combinations consisting of three dates of sowing (1st July, 11th July and 21st July) and two spacing (30×10 cm2 and 45×10 cm2). Pooled over two years results revealed that all the characters studied were markedly affected by sowing dates and row spacing. Data of all traits under studied were gradually decreased with delaying sowing date from 1st July to 21st July. The highest seed yield (12.19 q ha-1) was obtained when the crop sown on 1st July which was significantly superior to other dates of sowing. Closer row spacing gave statically higher seed yield than wider spacing. The interaction effects of dates of sowing×row spacing were found non-significant for all the traits studied. However, sowing of cluster bean on 1st July in a spacing of 30×10 cm2 gave the highest seed yield (12.74 q ha-1) as compared to other treatments. This may be due to higher number of pods plant-1, number of clusters plant-1, number of pods cluster-1, plant height and test weight.